416 Cervical carcinosarcoma with remission of malignant epithelial component but persisting stromal component after radiotherapy – One case report. (13th November 2020) - Sun, Y; Hung, K; Kang, C; Chang, S
Abstract : Introduction: Carcinosarcomas of the uterine cervix are rare. Herein, we report a woman diagnosed cervical carcinosarcoma with remission of malignant epithelial component but persisting stromal component after radiotherapy. Case report: A 30 y/o woman presented to our hospital with bulky cervical tumor FIGO stage IIIB. The cervical biopsy came from other hospital reported as adenocarcinoma. She was arranged for concurrent chemo radiation. However, Cisplatin was unable to give due to persisting pancyopenia after initiating radiotherapy. Bone marrow biopsy for her persisting pancytopenia disclosed acellular marrow. After completed external beam radiation therapy followed with brachytherapy, there is one cervical mass noted confined within the cervical canal, with biopsy disclosed sarcoma. She underwent abdominal total hysterectomy and bilateral salpingo-oophorectomy. Pathology revealed tumor cells with neuroectodermal differentiation, involving cervix, uterus and ovaries. After taken previous biopsy section together, a carcinosarcoma with heterogenous neuroectodermal component was inferred, while the components of adenocarcinoma have been eradicated by previous radiotherapy and the components with neuroectodermal differentiation survived due to resistance. Unfortunately, chemotherpay was not eligible before bone marrow transplantation and she still suffered from a progressive tumor recurrence and died 5 years later. Conclusion: The potential complexity and heterogeneity of cervical carcinosarcoma contributed to the variety of treatment modality. Such rapidly growing tumor may be responsive to radiotherapy and the role of chemotherapy may also be important, but their expected effects on the sarcomatous component may not be ideal. As a result salvage surgical intervention could be a therapeutic option for such locally advanced diseases.